“Goldilocks day”: identifying the optimal awake movement behaviour composition for predicted cardiometabolic health outcomes in youth - Joey Murphy; Charlotte Lund Rasmussen; Javier Brazo-Sayavera; Ademola Victor Damilola; Nastja Podrekar Loredan; Aoko Oluwayomi; Luís Bettencourt Sardinha; Niels Wedderkopp; Elaine Murtagh (Annals of Human Biology)
Background Most research focuses on the relationship of individual movement behaviours, neglecting how different compositions throughout the day associate with cardiometabolic health outcomes.Aim The aim of this study was to explore the optimal awake movement behaviour composition associated with predicted cardiometabolic health outcomes in youth.Subjects and methods The study included participants (N = 1,310 participants; 11.1 ± 2.5 [range = 7.98–17.1 years]; 55.9% female; 100% European) from the International Children’s Accelerometry Database. Accelerometer measured sedentary behaviour (SB), light-(LPA) and moderate-to-vigorous physical activity (MVPA) defined the awake movement behaviour composition. Four cardiometabolic health outcomes (lipid profile, blood pressure, glucose metabolism, and body mass) were assessed through nine parameters. These were regressed against the awake movement behaviour composition, adjusting for relevant covariates to estimate the optimal awake movement behaviour composition for each predicted cardiometabolic health outcome (i.e. “Goldilocks Day”).Results The final models found a significant relationship between the awake movement behaviour composition and cardiometabolic health outcome, excluding lipid profile indicators. For indicators of glucose metabolism, blood pressure and body mass, the Goldilocks Day consisted of less SB (–12 to −39 min), LPA (–8 to −32 min) and more MVPA (+44 to 47 min) when compared to the sample mean.Conclusion These findings concur with current guidelines that more MVPA and less SB are better, but the optimal time youth should spend in each behaviour depends on the health outcome of interest. This indicates that one size does not fit all when making recommendations for multiple cardiometabolic health outcomes.